RETHINKING FDI-LED GROWTH IN UZBEKISTAN: FROM SEZs AND INCENTIVES TO AN INSTITUTION-BASED INVESTMENT MODEL - Islomova Mufassal Muzaffarovna (Ecominds Press, 2025)
This paper examines the balance between foreign capital (FDI) and domestic investment in Uzbekistan’s industrial modernization. Evidence suggests that investment effectiveness depends on institutional quality and competitive discipline, whereas excessive incentives may entrench quasi‑monopolies and crowd out domestic capital. We argue for refocusing investment policy from inflow volumes to value‑added, localization and sustained outcomes, and outline priorities for mobilizing domestic resources (reinvestment, savings) alongside selective FDI.
Keywords: FDI; domestic investment; institutional environment; privatization; quasi-state sector; crowding‑in/out; investment policy